IMPLEMENTASI PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) KELAS IV SD NEGERI 005 TELUK PANTAIAN KECAMATAN GAUNG ANAK SERKA - Dede Desvina Pebriyanti; Andriansyah (Journal of Education and Culture (JEC), 2022)
Two stay two stray is a group learning system with the aim that students can work together, be responsible, help each other solve problems, and encourage each other to excel and train students to socialize well. Interest in learning is a desire or interest accompanied by attention and activity that gives birth to a sense of pleasure in changing behavior, both in the form of knowledge, attitudes and skills. This type of research is CAR which is carried out in two cycles, where in each cycle three meetings are carried out with four stages, namely, planning, implementing, observing, and reflecting. The subjects in this study were the fourth grade students of SD Negeri 005 Teluk Pantaian, totaling 28 students. Data collection techniques using observation, questionnaires, and documentation. The results of the study regarding the Implementation of Two Stay Two Stray Types of Cooperative Learning in Increasing Students' Interest in Natural Science Subjects Class IV SD Negeri 005 Teluk Pantaian, Gaung Anak Serka District, showed interest in learning before implementing two stay two stray cooperative learning of 54.17 with 'good enough' category. Therefore, it was continued with the first cycle by applying cooperative learning type two stay two stray of 59.99 with the category of 'good enough'. Based on these calculations, it is known that the increase is 5.82. Although there has been an increase but has not reached the expected target of 70, this research is continued with cycle II of 71.35 with the category of 'good', and has reached the expected target of 70, so this research is considered to be increasing. Based on these results, it can be concluded that the Implementation of Cooperative Learning Type Two Stay Two Stray Can Increase Student Interest in Natural Science Subjects Class IV SD Negeri 005 Teluk Pantaian, Gaung Anak Serka District.